Persiapan Menyusui Menurunkan Kejadian Putting Susu Lecet pada Ibu Nifas di Puskesmas Gandusari Kecamatan Gandusari Kabupaten Blitar - Maria Ulfa; Irma Noviana Tisnawati (Journal of Ners and Midwifery, 2016)
Breastmilk has advantages and privilages as a source of nutrients compared to other nutrient sources. However, the breastfeeding process often fail. The main cause of the failure is a problem in the breast. One of them are blisters on the nipples. Nipple blisters dominantly caused by breast feeding preparationespecially on breast feeding techniques and breastcare. The purpose of this study was to determine how is the preparation of breastfeeding lowers the incidence of nipple blisters of postpartum mother in Sub-district Health Centers Gandusari Kec.Gandusari Kab. Blitar. Methods: with posttest only control group design. The population in this study was 50 postpartum mother in Health Centers. The sample was 16 respondents by using purposive sampling. The independent variable was the preparation of breastfeeding, the dependent variable was the sore nipple blisters. The instrument used SOP. Result: the statistical Fisher Exact Probability Test showed p=0,003 (a=0,05). It could be concluded that the preparation of brestfeeding could reduce the incidence of nipple blisters postpartum mother in Sub-district Health Centers Gandusari. By this research, it was expected the respondents to actively ask, observing carefully about breasfeeding preparation especially breaastfeeding techniques and treatments given. So, breastfeeding in infants couldbe succeed. As for the profession of midwifery results of this study could be used as the input in motivating postpartum mother, so that it could perform the appropriate techniques of breastfeeding and breastcareto avoid nipple blisters.